Unpacking the Forces Behind Indonesia's Foreign Debt: What Drives Long-Term and Short-Term Borrowing? - Fadli, Faishal; Sagita S, Vietha Devia; Oktaviana, Yulis (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah, 2024)
Research Originality: This research explores the factors influencing Indonesia's foreign debt, providing insights into the long-term and short-term effects of inflation, exchange rates, the Fed Funds Rate (FFR), budget deficit, and exports. The originality lies in the comprehensive analysis of these variables using time series data from 2005 to 2022.Research Objectives: This study examines the impact of key macroeconomic variables on Indonesia's foreign debt, analyzing both long-term and short-term relationships to inform policy and future research.Research Methods: The study uses time series data from 2005 to 2022, applying the Error Correction Model (ECM) with EViews10 to analyze the dynamic relationships between foreign debt and the influencing factors.Empirical Results: The study finds that in the long term, exchange rates and exports positively influence foreign debt, while inflation has a negative impact. In the short term, only the Fed Funds Rate (FFR) negatively affects foreign debt. All variables are significantly influential in both the short and long term.Implications: These findings highlight the importance of managing inflation, exchange rates, and exports in the long term while considering the short-term impact of global financial conditions, such as the FFR, on Indonesia's foreign debt.JEL Classification: F34, E44, E31, F41, H63, C32